Dual release of a hydrophilic and a hydrophobic osteogenic factor from a single liposome. Issue 115 (8th December 2016) - Monteiro, Nelson; Martins, Albino; Pires, Ricardo A.; Faria, Susana; Fonseca, Nuno A.; Moreira, João N.; Reis, Rui L.; Neves, Nuno M.
Abstract : Dual release of growth/differentiation factors from liposomes induced osteogenic differentiation of mesenchymal stem cells. Abstract : Delivery systems may be designed to protect and control the release kinetics of growth/differentiation factors in a spatiotemporal manner. Liposomes are examples of biological-based bioactive agent delivery systems. In this work, ascorbic acid (AscA) was encapsulated in the inner compartment of the liposome and dexamethasone (Dex) was encapsulated within the lipid bilayer in order to develop a dual release system of these bioactive agents involved in the osteogenic differentiation of mesenchymal stem cells (MSCs). The particle size (∼150 nm) of the prepared liposomes showed a monodisperse distribution. The bioactive agent release study showed that Dex was released more rapidly from the liposomes than AscA. The Dex release profile showed an initial burst release within 12 h; afterwards, a slower and sustained release was observed until 21 days. The release of AscA from the liposomes was not detected until 6 h; afterwards, a linear release was observed from 24 h until 21 days. The effect of Dex–AscA-loaded liposomes on the viability, proliferation and osteogenic differentiation of human bone marrow-derived MSCs (hBMSCs) were assessed. The cell culture results showed that the Dex–AscA-loaded liposomes (in a single dose or in repeated doses) do not have any cytotoxic effect. Dex–AscA-loaded liposomes given once did not promote induction of hBMSCs differentiation into the osteogenic lineage. However, Dex–AscA-loaded liposomes given repeatedly promoted the hBMSCs differentiation into the osteogenic lineage, both in basal medium and complete osteogenic medium. These results were genotypically demonstrated by the expression of osteoblastic markers. In conclusion, Dex–AscA-loaded liposomes represent a biological nanoparticle strategy with potential safety and efficacy for bone tissue engineering approaches.